Hybrid Indicators for Fast and Sensitive Voltage Imaging. Issue 15 (8th March 2018) - Xu, Yongxian; Peng, Luxin; Wang, Sicong; Wang, Anqi; Ma, Ruirui; Zhou, Ying; Yang, Jiahe; Sun, De‐en; Lin, Wei; Chen, Xing; Zou, Peng
Abstract: Membrane voltage is an important biophysical signal that underlies intercellular electrical communications. A fluorescent voltage indicator is presented that enables the investigation of electrical signaling at high spatial resolution. The method is built upon the site‐specific modification of microbial rhodopsin proteins with organic fluorophores, resulting in a hybrid indicator scaffold that is one of the most sensitive and fastest orange‐colored voltage indicators developed to date. We applied this technique to optically map electrical connectivity in cultured cells, which revealed gap junction‐mediated long‐range coupling that spanned over hundreds of micrometers. Abstract : The fast and the sensitive : A hybrid strategy employing site‐specific protein modification techniques produced a palette of fluorescent membrane voltage indicators with sub‐millisecond response kinetics. These indicators enable the optical mapping of electrical communications among cells at high resolution.